Tantangan Dan Manfaat AI Dalam Perlindungan Data Kantor: Mengoptimalkan Keamanan Informasi - Joy Phillip Nehemia; Muhammad Rifky Hendrayana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The presence of artificial intelligence (AI) technology has revolutionized efforts to protect data in offices. The challenges organizations face in maintaining information security are becoming increasingly complex as technology advances, but the benefits of AI provide an effective solution to optimize information security. In this summary, we discuss the challenges and benefits of AI in office data protection, focusing on enhancing information security.The first challenge is the increasing complexity of cyber attacks. Attackers are constantly looking for new vulnerabilities and using more sophisticated attack techniques to breach security systems. Adequate data protection is needed to address this challenge and prevent unauthorized access to critical company information. Additionally, a lack of knowledge about managing and monitoring security systems is a major challenge for many businesses.However, the use of AI to protect office data offers several advantages. First, AI's ability to quickly and accurately detect security threats aids in early detection of cyber attacks. Predictive analysis supported by AI can also detect dangerous patterns and prevent attacks before they occur. Furthermore, using AI to automate security processes can optimize operational efficiency and accountability for events that occur. AI-based security can significantly reduce the risk of data breaches and cyber attacks.The use of AI technology in office data protection is not only a supportive tool but also an innovative and efficient solution to address increasingly complex challenges in information security. We hope this overview provides a deeper understanding of the challenges and benefits of AI in protecting office data, as well as efforts to optimize information security in this digital era.